Edukasi Bahaya Perilaku Seks Bebas Generasi Gen Z Di SMK Mathla’ul Anwar Sukalangu Pandeglang - Ucu Wandi Somantri (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Generation Z or the so-called Internet generation, the generation of teenagers who will replace the current Millennial generation, is expected to usher in a new era of technological development. Due to the strong influence of Internet technology, there are concerns that it will not only change the mindset of Generation Z, but also turn something taboo into an illegitimate social tradition. Developed and interesting educational activities about the risks of free sex are expected to provide enough knowledge to the younger generation so as not to do things that can endanger their reproductive health in the future. Generation Z Adolescent Reproductive Health Education Using the Edugame Method for Students of SMK Mathla’ul Anwar Sukalang, Pandeglang Regency. The results of this community service show that students are equally aware of the dangers of free sex. This method of educational and counseling games accompanied by animated videos is one of the persuasive activities that effectively make students aware of the dangers of free sex.